2013
DOI: 10.1371/journal.pone.0073587
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Mechanistic Profiling to Probe Small Molecule Binding to Sulfotransferases

Abstract: Drug metabolizing enzymes play a key role in the metabolism, elimination and detoxification of xenobiotics, drugs and endogenous molecules. While their principal role is to detoxify organisms by modifying compounds, such as pollutants or drugs, for a rapid excretion, in some cases they render their substrates more toxic thereby inducing severe side effects and adverse drug reactions, or their inhibition can lead to drug–drug interactions. We focus on sulfotransferases (SULTs), a family of phase II metabolizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 75 publications
2
27
0
Order By: Relevance
“…To date, only two in silico prediction models have been reported that utilize a structure-based approach including protein flexibility (28,63) and one of them proposed activity prediction for SULT subtype 1E1 (28). Both employ the strategy of performing MD simulations to sample the conformational space of different SULT subtypes as a basis for their prediction model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only two in silico prediction models have been reported that utilize a structure-based approach including protein flexibility (28,63) and one of them proposed activity prediction for SULT subtype 1E1 (28). Both employ the strategy of performing MD simulations to sample the conformational space of different SULT subtypes as a basis for their prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the enzyme structure, computational studies have investigated the mechanism of inhibition of SULT1E1 by nucleotides (25) and stereoselectivity of sulfonation via docking (26), analyzed the sulfonation reaction using QM/MM methods (27), and utilized molecular docking to predict ligand binding (28). Here, we report on a novel approach of computer-based metabolism prediction for human SULT1E1.…”
mentioning
confidence: 99%
“…Following a similar strategy, we expanded these studies to other SULT1 isoforms (Figure ). Our best models, introducing predicted protein‐ligand interaction energy by using molecular dynamics, docking and machine learning methodologies, showed accuracy of 67.28 %, 78.00 % and 75.46 %, for the isoforms SULT1 A1, SULT1 A3 and SULT1E1, respectively (accuracy here means the correct fraction or the percentage of correctly predicted inhibitors and non‐inhibitors). To the best of our knowledge, our protocol is the first in silico structure‐based approach consisting of a protein‐ligand interaction analysis at atomic level that considered both ligand structures and enzyme flexibility, along with a QSAR approach, to identify small molecules that can interact with phase II drug metabolizing enzymes.…”
Section: D‐admet: Overall Concepts and Applications In Mtimentioning
confidence: 97%
“…Recently, we have observed [44] that despite of very high druggability score of some holo Xray structures, the obtained enrichments are not always satisfactory. The druggability score is a useful evaluation but it might be not sufficient for a final selection of the best receptor conformations.…”
Section: Druggability Assessment Of the Generated Rcementioning
confidence: 99%
“…Another MD-based approach, Limoc, aims at sampling RCE appropriate for accommodating ligands, which are chemically and structurally diverse and thus unbiased toward a particular class of ligands [43]. Recently we performed successful ligand profiling of drug metabolizing enzymes sulfotransferases by employing docking to RCE generated by MD simulations combined with hierarchical conformational clustering of different binding site conformations [44].…”
Section: Introductionmentioning
confidence: 99%